Emancipatory Qur'anic Hadith Education in the Digital Age: A Critical Analysis of Learning Models in MTsN 1 Palangka Raya - Moh. Ali Muttaqo; Desi Erawati (Jurnal Studi Guru dan Pembelajaran)
The urgency of this research lies in the need to reconstruct a more humanist, fun, and liberating learning model of the Qur'an Hadith, in accordance with the needs of the times and the character of digital learners. This study aims to analyses the learning model of Al-Qur'an Hadith at MTsN 1 Palangka Raya by using Paulo Freire's Critical Mazhab approach, as well as identifying opportunities and challenges in implementing dialogical learning and building critical awareness (conscientização). The method used is qualitative research with a case study approach. Data collection techniques were conducted through observation, in-depth interviews and documentation, while data analysis used descriptive-critical techniques based on Freire's theory. The results show that although some teachers have realized the importance of a dialogical approach and started using digital technology, the learning model is still dominated by the banking education pattern. Students are still positioned as passive recipients, with little room for discussion and reflection on the meaning of Qur'anic teachings in the context of real life. The main obstacles include limited time, lack of teacher training, and strong old pedagogical habits. The implication of this research is the need for pedagogical transformation through critical education-based teacher training, contextual curriculum development, and creative integration of digital technology as a dialogical medium. Thus, Al-Qur'an Hadith education is not only a means of mastering the text, but also an empowerment tool to form critical, active, and contributive learners in the digital era.